Structural Equation Modeling for Men's Cosmetics Behavior Research - Shimpi, Siddharth Shriram (Indian Journal of Marketing, 2016)
The descriptive study examines consumer behavior for men's cosmetics purchase in Pune region. A structured and undisguised questionnaire was developed to collect the primary data from 563 respondents. This study provides evidence and detailed insights on various elements used for an analysis and revealed that Attitude, Beliefs in Product Attributes, Self-Image, and Normative Influences positively affected Purchase Intention for Men's Cosmetics in Pune region. However, the present study does not pervade the scope of any particular cosmetics categories, brands, specific companies, and/or their products.